1986
DOI: 10.1002/hep.1840060330
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of human liver alcohol and aldehyde dehydrogenases, and their relationship to alcohol metabolism and alcoholism

Abstract: It is now widely accepted that the various pharmacologic and addictive consequences of alcohol consumption are related to the tissue concentration of ethanol or its metabolic products. The oxidative metabolism of ethanol in liver is principally catalyzed by alcohol dehydrogenase and aldehyde dehydrogenase. Both of these enzymes exist in multiple molecular forms, and genetic models have been proposed to account for the multiplicity of isoenzymes. Alcohol dehydrogenase subunits are encoded at five different gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
339
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(351 citation statements)
references
References 72 publications
10
339
0
2
Order By: Relevance
“…The hazard ratio of hospitalization for alcoholism in men and women with the slow alcohol degradation ADH1B Á 1/1 genotype was 3.9 (95% CI: 1.0-16) and 2.7 (95% CI: 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hazard ratio of hospitalization for alcoholism in men and women with the slow alcohol degradation ADH1B Á 1/1 genotype was 3.9 (95% CI: 1.0-16) and 2.7 (95% CI: 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…3 Well-known functional polymorphisms of ADH1B and ADH1C may explain this finding because the ADH1B Á 2 vs the ADH1B Á 1 allele confer a 38-fold increase in in vitro alcohol degradation rate (that is, the conversion of ethanol to acetaldehyde) and the ADH1C Á 1 vs the ADH1C Á 2 allele confer a 2.5-fold increase in in vitro alcohol degradation rate. 4 During alcohol degradation, acetaldehyde is only found in low concentrations. If concentrations become high, for example, during treatment with disulfiram (used in some countries to prevent alcohol intake among alcoholics) or in individuals with a defective acetaldehyde dehydrogenase (found among Asians), individuals experience severe nausea and flushing and automatically abstain from drinking alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…The ADH2-2 allele, which encodes the more active b2-subunit, is more prevalent in Asian populations (60 -80%) than Caucasians (0 -10%) (Goedde et al, 1992) and leads to an increased metabolic rate in vitro (9.2 min 71 for b1b1 and 400 min 71 for b2b2 isoenzymes) (Bosron and Li, 1986). Furthermore, the ADH2 polymorphism has been shown to increase the alcohol elimination rate after alcohol consumption (Thomasson et al, 1993) and to influence the metabolism of alcohol in peripheral tissues (Takeshita et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…1 When ethanol is consumed, it is metabolized primarily by alcohol dehydrogenase (ADH) into acetaldehyde, an intermediate metabolite, and then it is metabolized by aldehyde dehydrogenase (ALDH) into acetic acid. 2 Acetaldehyde, a well-known carcinogen in animals, has an important role in alcohol toxicity in humans. 3 Most studies, conducted mainly in Japan, have revealed associations between the ADH2 or ALDH2 polymorphism and esophageal cancer risk.…”
Section: Introductionmentioning
confidence: 99%